HUBUNGAN KUALITAS INFORMASI AKUN INSTAGRAM @SEPUTAR.AESPA DENGAN PEMENUHAN KEBUTUHAN INFORMASI FOLLOWERS - Noorallifa Adhienda Putri; Prijana Prijana; Asep Saeful Rohman (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2022)
This study discusses the quality of Instagram account information @seputar.aespa by meeting the information needs of followers. The purpose of the study is to determine whether there is a significant correlation between the account's relevancy, accuracy, timeliness, and completeness of information with the fulfillment of the information needs of followers. The population of this research is 241 active followers of the Instagram account @seputar.aespa. With a simple random sampling method, the study was able to collect 150 samples. The research method used is a survey with a quantitative approach. Online questionnaires were then spread and conducted to gather the data for this study. The analysis technique used is descriptive data analysis and inferential analysis of the Pearson Product Moment correlation test. The results of the study indicate that there is a significant correlation between the relevancy, accuracy, timeliness, and completeness of information on the Instagram account @seputar.aespa and the fulfillment of information needs of followers. The conclusion is @seputar.aespa Instagram account is considered a good source of information for the followers. The Instagram account @seputar.aespa provides relevant, accurate, timeliness, and complete information to meet followers' information needs.